Biotechnology and Sustainable Livelihoods - Findings and Recommendations of an International Consultation - Falck-Zepeda, José B.; Cohen, Joel I.; Meinzen-Dick, Ruth S.; Komen, John (International Service for National Agricultural Research, 2002)
This Briefing Paper summarizes the outcome of a consultation organized by ISNAR's Biotechnology Service (IBS) in June 2001 to examine various approaches and case-study projects relating to the assessment of the socioeconomic impact of biotechnology on the poor in developing countries. Following the introduction of the ""sustainable livelihoods framework"" (developed by DFID, the UK Department for International Development) as the basis for further assessments of agricultural biotechnology inputs, research scientists and representatives from participating institutions, CGIAR centers, and donor and development agencies worked together to design and develop a joint project titled ""Biotechnology and Sustainable Livelihoods-Examining Risks and Benefits.""